ChemInform Abstract: Beyond Post‐Synthesis Modification: Evolution of Metal—Organic Frameworks via Building Block Replacement. Issue 43 (21st October 2014) - Deria, Pravas; Mondloch, Joseph E.; Karagiaridi, Olga; Bury, Wojciech; Hupp, Joseph T.; Farha, Omar K.
Abstract Review: 132 refs.